The exchange : after The Firm - Grisham, John ([The Firm, 2023)
In this explosive sequel to The Firm, Mitch, a partner at the largest law firm in the world, is asked for a favor by a mentor in Rome that plunges him into a sinister plot that has global implications and once against places everyone he holds dear in danger.